Conservation agriculture, nitrogen and residual sulphur effects on maize (Zea mays) growth and yield in a long-term maize-Indian mustard (Brassica juncea) system - ROY, ARKAPRAVA; DAS, T K; DASS, ANCHAL; BHATTACHARYYA, RANJAN; BHATIA, ARTI; MAITY, PRAGATI PRAMANIK; SUDHISHRI, SUSAMA; RAJ, RISHI; G, PRABHU; SEN, SUMAN; RATHI, NEELMANI; SHARMA, TARUN; et al. (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during rainy (kharif) seasons of 2020–21 and 2021–22 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to assess the effects of nitrogen and residual sulphur (S) on maize crop in the 11th year of a long-term conservation agriculture (CA)-based maize (Zea mays L.)-Indian mustard [Brassica juncea (L.) Czern.] cropping system. The CA-based practice CA3 [ZT maize (ZTMz) + mustard residue (MsR) + brown manuring (BM) – ZT mustard (ZTMs) + maize residue (MzR)] resulted in greater maize plant height and dry weight than other CA and CT systems except CA4 [ZTMz + mungbean residue (MbR) – ZTMs + MzR – ZTMb + MsR], which had comparable plant height and dry weight. The CA3 increased maize dry weight by 9% and 11.7% over CT in 2020–21 and 2021–22, respectively. On the contrary, CA4 exhibited highest root length, root mass, and root volume densities in both years, and CA3 was comparable. It gave significantly higher grain yield than other treatments except CA3 and CA2 (ZTMz + MsR- ZTMs + MzR), which were comparable. The 100% and 75% recommended dose of N gave comparable grain yield under all CA-based treatments, indicating a saving of 25% N ( 37.5 kg N/ha), mainly under CA practices. This highlights N economization over times in CA system. The 100% and 50% S applied to mustard could not show any significant residual effect on maize grain, stover and biological yields. Interactions between CA practices and N treatments for grain yield was significant but between CA and residual S, treatments were statistically similar. Thus, this study underscores the importance of CA framework for enhancing yield and income through better N and S management/savings in maize-mustard system.